Growth rate of Scenedesmus acutus (Meyen) in cultures exposed to trifluralin - Cetin, A. K.; Mert, N. (Hard, 2006)
The objective of this study was to determine the effect of trifluralin on the growth of Scenedesmus acutus in comparison to growth without trifluralin during 5 days. For growth in trifluralin 20-40 mu g/L, four days of S. acutus growth occurred compared to growth in the absence of trifluralin. This decrease in growth in S. acutus was correlated with an increased amount of trifluralin concentration. At trifluralin concentration of 60 mu g/L, growth was maintaned for three days. S. acutus in the presence of at 80 mu g/L trifluralin showed one-day growth. It was concluded that increasing trifluralin concentration decreased growth of S. acutus in a dose-dependent manner.
Keywords: trifluralin; algal sensitivity; Scenedesmus acutus